Community Preparedness in Facing Fire Disasters in Pondok Karya Village, Pondok Aren District, South Tangerang City - Rahman, Fathin Aulia (Universitas Lambung Mangkurat, 2024)
Pondok Aren sub-district is the area where fires occur most frequently in South Tangerang, with 16 incidents, 10 incidents due to electrical short circuits, and more than 80 rescue operations during 2022. Pondok Karya sub-district is an area with a high population density, making it prone to fires. This research aims to analyze the level of community preparedness for facing fire disasters in Pondok Karya Village. The method used in this research is quantitative-descriptive. The population in this research are people who live in Pondok Karya Village. The sampling technique used was purposive sampling with a sample size of 100 people. Data collection methods use questionnaires, observation, and documentation. The analysis technique uses descriptive percentages. The research results are based on five parameters: knowledge and behavior in dealing with disasters, emergency response plans, early warning systems, resource mobilization, and social capital. The research results show that the level of community preparedness for fire disasters is relatively low. The most influential factors are traditional-based early warning system indicators, socialization of early warning system mechanisms, and disaster organizations at the local level.